Pemadatan Ngremo Konvensional Pertunjukan Ludruk Menuju Pertunjukan Seremonial Torism - Wahyudiyanto Wahyudiyanto; Pundjul Pitono (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2023)
The presentation of the Ngrema dance in the Ludruk performance takes a relatively long time, especially in the part of the interlude structure because there are nyawer spectators and involved in nayub in the presentation. In this era of tourism that respects time, long presentations of art are no longer interesting to show, therefore a Lecturer at the Sekolah Tinggi Kesenian Wilwatikta Surabaya held community service activities by providing socialization of compact Ngrema at the pendapa of the East Java Cultural Park in Surabaya as a result of the revitalization of Ngrema Ludruk Karya Mojokerto culture. The methods used are demonstration and drill in the process of condensing motion material, chants, and music in each part of the Ngrema Ludruk performance structure. The result of this community service was Ngrema Ludruk in compact form which received high appreciation and enthusiasm from the Ludruk community and the audience in general.